(untitled) (Agricultural Engineering, 2023)
This paper presents a method of utilizing a transition curve in planning the movement trajectory of agricultural machinery during the headland turns. The approach involves using the transition curve, whose curvature and tangent angle are described by the trigonometric function. For the designed course, the kinematic quantities, wheel turning angles, and their rates of change were determined for two models of agricultural tractors. The algorithm proposed in this study ensures continuity and smooth changes in the kinematic quantities and can be applied to the trajectory planning of agricultural implements and machines, autonomous vehicles, mobile robots, manipulators, and CNC machines.